Method for producing graphitized nanoporous carbon, carbon particles thus obtained, and use thereof as highly stable supports for electrochemical processes

Through a simplified preparation method, nanoporous carbon materials with highly graphitized and mesoporous structures are prepared by using the transition metal salt in resorcinol-formaldehyde gel and iron acetylacetonate, which solves the problems of high production costs and complex processes in the prior art, and realizes the preparation of high-performance carbon materials, which are suitable for catalyst support in electrochemical methods.

CN119585200APending Publication Date: 2025-03-07KOHLER RES NONPROFIT LLC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380050778.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-01
Filing Date
2023-06-20
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, when preparing high-performance carbon materials for electrochemical methods, there are problems such as high production costs, complex processes and difficult to expand, and the obtained materials do not meet high-standard performance requirements.

Method used

Using a simplified preparation method, a one-pot reaction, filtration, drying, carbonization and leaching are carried out by introducing transition metal salts such as iron salts in resorcinol-formaldehyde (RF) gels, using iron acetylacetonate as a pore-generating agent and graphitizing agent, to form graphitized nanoporous carbons.

Benefits of technology

The preparation of carbon materials with high graphitization and mesoporous structures has been achieved. The materials have high stability and conductivity and are suitable for catalyst support in electrochemical methods, especially in PEMFCs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585200A_ABST
    Figure CN119585200A_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing graphitized nanoporous carbon, to the carbon particles thus obtained, and to the use thereof as highly stable supports for electrochemical processes.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method for preparing graphitized nanoporous carbon, the carbon particles obtained therefrom, and their use as highly stable supports for electrochemical processes.

[0002] Carbon materials are widely used catalyst support materials in electrochemical processes due to their high conductivity, stability and availability. For polymer exchange membrane fuel cells (PEMFCs), platinum on carbon black and its alloys are state-of-the-art catalysts. Hollow graphite spheres (HGS) as disclosed in WO 2013 / 117725A1 combine the advantages of carbon black with their uniform morphology and porosity determined in the low mesopore range. By confining metal nanoparticles (NPs) into the pores, PtM / HGS The catalyst has shown resistance to common degradation pathways of nanoparticle agglomeration and dissociation, which ultimately makes the catalyst superior to commercially available alternatives. In addition, small mesopores have recently been characterized to aid gas transport and resistance of PEMFC catalysts to ionomer poisoning, making HGS an even more promising catalyst support. The synthesis of HGS involves chemical vapor deposition of ferrocene into the pores of a hard template, followed by annealing and subsequent leaching of the hard template with hydrofluoric acid. This sequence, while highly controlled, is not very economical and is virtually impossible to scale up.

[0003] In the prior art, methods for preparing resorcinol-formaldehyde structures are known. For example, Gaikwad Mayur M. et al. disclosed "Enhanced catalytic graphitization of resorcinol formaldehyde derived carbon xerogel to improve its anodic performance for lithium ion battery" in Materials Today Communications, Vol. 20, September 1, 2019, p. 100569.

[0004] Similarly, CHEN LING et al. disclosed “Hierarchical porous graphitized carbon xerogel for high performance supercapacitor” in DIAMOND AND RELATED MATERIALS, ELSEVIER SCIENCE PUBLISHERS, AMSTERDAM, NL, Vol. 121, December 20, 2021, p. 2021.108781.

[0005] However, it is common that the obtained structures show the expected properties, but they do not meet the requirements of high-standard materials for electrochemical purposes, which still needs to be improved.

[0006] It is therefore an object of the present invention to provide a material which retains the beneficial properties of HGS, namely their high graphitization and well-defined porosity in the low mesopore range, and which can be produced more economically.

[0007] The problem of the present invention is solved by providing a method for preparing graphitized nanoporous carbon, the carbon obtained thereby, and its use as a highly stable support for electrochemical processes, in particular derived from resorcinol-formaldehyde (RF) gel, which allows a significant simplification of the preparation sequence.

[0008] The main inventive aspect of the synthetic method of the present invention is to use a scalable and simple reaction sequence to form graphite and mesoporous carbon structures simultaneously. In more detail, the mesopores are in a size range that can limit the holes of metal nanoparticles (1-10nm) and are located inside the carbon matrix (intragranular pores), rather than between separate particles. This clear porosity can limit the holes of active metals, so that the catalyst shows excellent stability for electrochemical degradation. In addition, the procedure does not rely on the laborious steps used by the prior art, such as supercritical drying, freeze drying or solvent exchange, so the economy is also better than the alternatives reported previously.

[0009] In more detail, the present invention relates to a method for preparing graphitized nanoporous carbon, comprising the steps of:

[0010] a) Prepare the following mixture in a solvent:

[0011] i) a nucleophilic compound selected from the group consisting of melamine, melam, melem, ammeline, 4,6-amino-dihydroxy-1,3,5-triazine, aminophenol, diaminobenzene, dihydroxybenzene, trihydroxybenzene and any combination thereof,

[0012] ii) formaldehyde or an oligomer thereof in a stoichiometric excess relative to compound i) for complete polymerization,

[0013] iii) a metal graphitization catalyst, wherein the molar ratio of the metal graphitization catalyst to compound i) is from 1:30 to 1:3, optionally from 1:10 to 1:3, wherein the metal graphitization catalyst is selected from Fe salts, Co salts or Ni salts of organic acids or acidic organic compounds, in particular Fe formate, Fe oxalate, Ni oxalate, Ni formate, Co oxalate, Co formate, Fe(II)(acac) 2 、Fe(III)(acac) 3 、Ni(II)(acac) 2、Co(II)(acac) 2 、Co(III)(acac) 3 or any combination thereof, and optionally

[0014] iv) a catalytic amount of a promoter compound, preferably ammonia,

[0015] The solvent contains water and C 1 -C 3 Aliphatic alcohol, wherein the volume ratio of water is 0 volume % to 100 volume % relative to the total volume of the solvent, and the balance is C 1 -C 3 aliphatic alcohol; the solvent is preferably an aqueous solution having a 10-40% by volume content of the C 1 -C 3 Aliphatic alcohols;

[0016] b) heating the mixture obtained in step a) to a temperature of 30° C. to 100° C. and maintaining the mixture in this temperature range for at least 6 hours, preferably 6 to 60 hours, more preferably 6 to 50 hours,

[0017] c) separating the reaction product obtained in step b) from the aqueous solvent, optionally grinding the separated reaction product and optionally washing the separated reaction product with fresh aqueous solvent;

[0018] d) subjecting the separated reaction product obtained in step c) to a high temperature graphitization process at a temperature ranging from 600° C. to 1000° C., thereby providing a graphite skeleton;

[0019] e) subjecting the graphitized product obtained in step d) to a process for leaching out the metal of the metallic graphitization catalyst, preferably by treatment with a mineral acid; and

[0020] f) Water and C 1 -C 3 The reaction product obtained in step e) is washed with an aliphatic alcohol and the washed product is finally dried, followed by an optional grinding step.

[0021] In the process of the present invention, a catalytic amount of a promoter compound can be used to promote or start the condensation process. As a promoter compound, a weakly acidic or basic compound such as sodium carbonate, sodium bicarbonate can be used. Ammonia is preferably used because it evaporates completely during the carbonization process.

[0022] The solvent used for the condensation comprises water and C 1 -C 3 aliphatic alcohol, and relative to the total volume of the solvent, the volume ratio of water is 0 volume % to 100 volume %, and the balance is C 1 -C 3aliphatic alcohol; the solvent preferably has a content of 10-40% by volume of the C 1 -C 3 An aqueous solution of an aliphatic alcohol. The alcohol is preferably ethanol.

[0023] In the process of the present invention, the nucleophilic compound is selected from melamine, melam, melem, ammeline, 4,6-amino-dihydroxy-1,3,5-triazine, aminophenol, diaminobenzene, dihydroxybenzene, trihydroxybenzene and any combination thereof, and is reacted with a stoichiometric excess of formaldehyde or its oligomers relative to compound i), which allows essentially complete polymerization / condensation of compound i) with formaldehyde to form a polycondensed network.

[0024] In a further detailed method of preparing graphitized nanoporous carbon, the additional steps are included:

[0025] g) impregnating the graphitized nanoporous product obtained in step f) with a catalytically active metal selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Mo, Se, Sn, Pt, Ru, Pd, W, Ir, Os, Rh, Nb, Ta, Pb, Bi, Au, Ag, Sc, Y, preferably Pt, Ru, Pd, Au, Ag, Ni, Co, Ir, including their salts and mixtures thereof, in the form of a solution of a metal salt or a mixture thereof, preferably by incipient wetness,

[0026] h) subjecting the graphitized nanoporous product obtained in step g) to a hydrogenation process, thereby forming catalytically active metal sites;

[0027] i) subjecting the graphitized nanoporous product obtained in step h) to a further temperature treatment in an atmosphere inert to the metal particles and the graphitized nanoporous product at a high temperature range of 600°C to 1400°C, preferably 600°C to 1000°C, thereby changing the microstructure and confining the catalytically active metal sites in the mesopores, thereby improving the chemical and electrochemical properties.

[0028] In one embodiment of the process according to the invention, compound i) is selected from resorcinol, melamine and derivatives thereof, in particular resorcinol.

[0029] In another embodiment of the process of the present invention, the metal graphitization catalyst is selected from Fe(II)(acac) 2 ,Fe(III)(acac) 3 , Ni(II)(acac) 2, Co(II)(acac) 2 ,Co(III)(acac) 3 or any combination thereof.

[0030] In yet another embodiment of the process of the present invention, the concentration of compound i) in the solvent is 0.01 mol / L to 0.5 mol / L, and the mixture is stirred in step b).

[0031] In a further embodiment of the process according to the invention, the concentration of compound i) in the solvent is 0.5 mol / L to 2.0 mol / L and the mixture is not stirred in step b). The product obtained in most cases requires grinding due to its lumpy structure.

[0032] The present invention also relates to graphitized nanoporous carbon particles obtainable according to any of the aforementioned methods, and their use as catalysts, in particular for the cathode-side oxygen reduction reaction (ORR) in PEM fuel cells.

[0033] Step i), wherein the metal-loaded graphite particles obtained in step h) are further treated / heat-treated at a high temperature range of 600-1400°C, preferably 600-1000°C, preferably for a period of 1-10 hours, more preferably 1-5 hours, and preferably carried out under an inert atmosphere such as argon, in order to change the microstructure of the particles and promote the confinement of the metal particles in the pore structure, which is particularly important for improving the electrochemical stability of the nanoparticles under harmful potential cycling conditions.

[0034] After the leaching step, graphite mesoporous particles are obtained, which can be impregnated in a further step with a salt solution of a catalytically active metal (e.g. Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Mo, Se, Sn, Pt, Ru, Pd, W, Ir, Os, Rh, Nb, Ta, Pb, Bi, Au, Ag, Sc or Y or any combination thereof, preferably Pt, Ru, Pd, Au, Ag, Ni, Co or Ir) in an impregnation step, wherein the entire volume of the metal salt solution, preferably a chloride solution, or any combination of salt solutions is completely absorbed in the mesopores of the graphite particles, and which can optionally be dried. The impregnation can be accomplished by using an alcoholic solution of a metal salt in such an amount that the loading of the particles with the catalytically active metal is 10-40% by weight, based on the total weight of the final dry particles.

[0035] There is no limitation on the catalytically active metal that can be used in the mesoporous graphite particles according to the present invention, and it can be one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Mo, Se, Sn, Pt, Ru, Pd, W, Ir, Os, Rh, Nb, Ta, Pb, Bi, Au, Ag, Sc, Y or any combination thereof. Suitable metals can vary depending on the reaction to be performed by the metal-loaded graphite particles according to the present invention. In addition, the metal can be a single metal or an alloy of two or more metals.

[0036] The graphite particles thus obtained, loaded with metal precursors or, in the case of alloys, with a mixture of metal precursors, are subjected to a hydrogenation process, which is preferably carried out as gas phase hydrogenation. Such a gas phase reduction can be carried out at elevated temperatures of 100-500° C. in the normal pressure range. By this hydrogenation, metal clusters are formed in the mesoporous structure of the graphite particles. Thereafter, a heat treatment step carried out at elevated temperature defines the final microstructure of the metal or alloy nanoparticles and promotes pore confinement to improve the chemical and electrochemical properties.

[0037] To accomplish the present invention, the inventors analyzed the options for preparing suitable carbon supports. For example, resorcinol-formaldehyde gels are polymers prepared by the polycondensation of resorcinol and formaldehyde. Their synthesis is multifaceted, as changes in pH, temperature, solvent, drying conditions, and added salts, bases, or acids produce polymers with different morphologies. Due to their high surface area and adjustable porosity, carbonized RF gels have been studied in the prior art for use in electrochemical devices such as supercapacitors or batteries. For PEMFC, RF gels are considered as support materials, but with little success, which may be due to their low graphitization and high micropore volume. The existing literature describing the synthesis of RF gels is large, and both mesoporous and graphitized carbon materials derived from RF gels and their combinations are generally described. In order to analyze the reasons why none of these materials can compete with carbon black for use as a support for PEMFC, the characteristics of the RF system will be described in more detail below.

[0038] The preparation of RF polymers can follow a sol-gel approach. First, hydroxymethylresorcinol is formed by the reaction of resorcinol and formaldehyde. Subsequently, these polyols are concentrated with the removal of water to form dispersed nanometer-sized clusters, also called sols. Sols are usually aged at elevated temperatures in closed containers to prepare gels. Gels are three-dimensional, highly porous, fractal structures of individual primary particles that generally retain their impressive morphology. For this purpose, supercritical drying (e.g. with CO ) is applied. 2 ) to form an aerogel, retaining up to 90% of the gel volume. In some cases, drying can be performed by freeze drying with similar success, the term being cryogel. If this complex drying technique is to be avoided, subcritical drying is used to produce xerogels, polymers with a collapsed but still substantial pore structure. Alternatively, if the synthesis is carried out at high dilution and with agitation, individual spheres can be prepared, similar to the preparation of monodisperse silica spheres. method.

[0039] For use in electrochemical devices, the RF gel must be conductive and therefore carbonized and potentially further activated to tune the properties of the RF-carbon. The molecular composition of the gel depends on the benzene rings of resorcinol and therefore retains a large amount of solid and porous structure under carbonization. The carbonized RF spheres have porosity in the microporous region without any aggregate structure of the primary particles. These pores are due to the reaction products such as water, CO and CO 2 Formed by escaping from the bulk polymer during the transformation to carbon. RF-gels are the preferred precursors for the preparation of mesoporous RF carbons. Since the size and connectivity of the primary particles forming the gel are highly tunable, the pores can be generated in the junctions of these clusters or as pockets in the gel structure. By varying the synthetic procedure, RF carbons with pore sizes throughout the mesoporous range have been prepared in the prior art. However, it is critical to mention that the pore size distribution is generally broad and that the pores are different from those typical of hollow graphite spheres in that they are not located in the particles but in the edges and corners of small fractal primary particles. Therefore, if confining the metal in these mesopores can provide the same stability enhancement known from HGS (whose mesoporosity is intraparticle), this is ultimately problematic. Similar considerations exist in the improved transport properties and protection against ionomer poisoning achieved by mesoporous supports. RF gels with intraparticle porosity have been reported using surfactants or hard templates, but, despite the highly defined textures obtained, the synthetic sequence is complex and has the disadvantages of HGS preparation described previously.

[0040] Increasing the conductivity of RF carbons by graphitization as performed herein provides a suitable route to improve their suitability for electrochemical processes, where the high stability and conductivity of graphitic carbon are beneficial. In the prior art, the conductivity of different RF xerogels carbonized at 800°C was compared with carbon black, and it was found that the conductivity of carbon black was 10 times higher, which was independent of the composition of the xerogel. High temperature carbonization and the addition of a graphitizing catalyst before annealing are ways to increase the graphitization of RF carbons. If no catalyst is used, temperatures well above 2000°C are generally required to form graphitized carbon from the polymer. Therefore, most transition metal catalysts such as iron or nickel are included in the RF-polymer before carbonization, either by addition to the synthesis mixture or by post-impregnation of the polymer. Although graphitic carbon has been prepared from RF polymers by these methods, the flexibility of the synthesis is significantly reduced. If metal salts are integrated into the synthesis mixture, the complex reaction mixture will in any case require further balancing, for example to offset the effect of acidic metal salts on pH. Post-impregnation could serve as an alternative, but it adds another step to the synthesis and may have a less significant effect on graphitization since the catalyst is deposited on the carbon surface rather than in the structure itself.

[0041] In summary, the preparation of RF carbons is highly tunable and the relevant literature is extensive. However, in the prior art, the synthesis of mesoporous graphitic RF carbons relies on the use of hard templates, surfactants or large amounts of metal salts. In addition, additional steps such as complex drying, hydrothermal treatment, post-impregnation or activation complicate the essentially simple reactions. Therefore, the study of simple synthetic routes to graphitic mesoporous RF carbons is highly relevant. If a simple, scalable preparation sequence as provided by the present invention is found, the carbon is a good candidate for electrochemical methods, especially as a support material for PEMFC catalysts.

[0042] As shown herein, the inventors synthesized graphitic RF spheres by introducing transition metal salts such as iron salts into the RF synthesis mixture. The inventors showed how different salts affect the pH of the mixture and the effect on the polymer morphology. Finally, using ferric acetylacetonate as a combined porogen and graphitizing agent, the inventors proposed a scalable synthesis of mesoporous and highly graphitized carbon spheres (GRF). The inventors did not require a hydrothermal step and dried overnight in air and thus avoided solvent exchange, supercritical drying or activation post-treatment. Using XRD, TG-MS, N 2 GRF was comprehensively characterized by physical adsorption and TEM. Subsequently, the inventors loaded GRF (Pt / GRF) with metal nanoparticles, such as platinum nanoparticles, and evaluated the material as a catalyst for oxygen reduction reaction (ORR). Pt / GRF has an activity comparable to that of industrially known carbon black-supported Pt, while being significantly more stable in an accelerated degradation test (ADT). Due to the simple and scalable synthesis procedure and the beneficial morphology of GRF, which is similar to highly stable HGS, the inventors consider GRF as a potential candidate for industrial applications.

[0043] Experimental Section

[0044] The present invention is further described by means of the accompanying drawings and examples. In the accompanying drawings, the corresponding figures show:

[0045] Figure 1 : a) Simplified reaction scheme for the polycondensation of resorcinol and formaldehyde. b) Overview of different synthetic routes for RF spheres or RF gels.

[0046] Figure 2 : 1.0M aqueous solution with salt (pH 水 ) compared to the reaction mixture (pH Rct-Sol ) pH overview. In the following table, exemplary digital pictures of the polymers are provided. Due to the low solubility of ferric acetylacetonate in water, the salt was not completely dissolved, so the measured pH represents the value of a saturated solution of the salt.

[0047] Figure 3:After carbonization and leaching, the original Fe(acac) 2 Preparation of RF polymers 2 Comparison of physical adsorption isotherms (left) and XRD patterns (right). For the "leached" and "carbonized" states, the intensity of the XRD patterns was normalized to the (002) reflection of graphite (~26°), while the patterns derived from polymer analysis were plotted as absolute intensity. After graphitization, a significant increase in porosity was observed. In addition, the (002) reflection (~26°) in the XRD pattern indicates the formation of graphitic carbon.

[0048] Figure 4 : TEM micrographs at different magnifications of CRF prepared with iron acetylacetonate. In contrast to the reference material prepared without using iron salts (CRF-Ref, left), the formation of a porous, highly graphitic structure has been observed.

[0049] Figure 5 :Through a) XRD, b) Raman spectroscopy and c) N 2 The characterization of CRF prepared by physical adsorption is summarized. In addition, in Table d), the 0 The relevant properties measured, such as the external surface area (Ext.SA), micropore volume (V P,微 ) and total pore volume (V P,总 ). In both XRD and Raman spectra, it has been observed that CRF-Fe(acac) 2 and CRF-Fe(acac) 3 is highly graphitized. A large difference in porosity is similarly visible, as the sample prepared with Fe is mainly mesoporous, while CRF-Ref is almost entirely microporous.

[0050] Figure 6 :Polymer RF-Fe(acac) 2 Summary of TG-MS measurements in argon. The mass loss is indicated in the upper part, while the ion counts of selected fragments are shown below. In contrast to the reference material without iron salt (right), a sharp mass decrease is observed at 600 °C. This shows the porogenic effect of the acetylacetonate ligands under graphitization and explains the observed mesoporosity of the carbon material.

[0051] Figure 7 : Using Co and Ni acetylacetonate through N 2 Characterization of GRF prepared by physical adsorption. Isotherms are shown. Similar to the material prepared using Fe(acetylacetonate), the porosity of the carbon is primarily in the mesoporous range expected for ORR catalyst supports, but when using Ni(acac) 2 As iron salts, materials with overall lower porosity are obtained.

[0052] Figure 8 : Comparison of XRD patterns of Pt nanoparticles (NPs) deposited on GRF (left). Carbon GRF by RF-Fe(acac) 2 Pt NPs were prepared by graphitization and subsequent leaching with HCl. 2 PtCl 6 The GRF was prepared by incipient wetness impregnation of an aqueous solution of and then annealing at the specified temperature for 2.5 h. TEM micrographs of samples annealed at 750 °C and histograms of Pt particle size distribution are also provided. The Pt NP size can be adjusted by varying the annealing temperature. The NPs are deposited into the pore system of the GRF and if annealed at 750 °C, they are deposited to an average size of 2.8 ± 1.0 nm, which is within the optimal range for Pt-based ORR catalysts.

[0053] Fig. 9 : Overview of the activity (left) and stability (right) of the Pt / GRF catalyst for catalyzing the ORR, which was determined by evaluation in a rotating disk electrode (RDE) half-cell setup. The mass activity (MA) was calculated from the current at 0.9 V (RHE) at a rotation frequency of 1600 rpm. The ECSA was determined by CO stripping. The specific activity (SA) was calculated from the MA and the ECSA. For the stability studies, the catalysts were subjected to an accelerated degradation scheme consisting of 20,000 square wave cycles from 0.6 to 1.0 V (RHE) with a hold time of 1 s. The ECSA was determined by CO stripping after the specified number of cycles. As a comparison, the same treatment was performed on a catalyst consisting of Pt NPs on VulcanXC 72R. More details can be found in the experimental section. The Pt / GRF catalyst shows high activity for the ORR and a stability of about 100 m 2 g -1 Pt The stability of Pt / GRF under potential cycling is better than that of Pt NPs supported on commercial carbon black, and the ECSA has a lower drop of ∼15%, which is in contrast to the >30% loss of Pt / V.

[0054] Fig.10 : XRD of GRF and GRFG (upper left) and N 2 Comparison of physical adsorption data (lower left) and micrographs of GRFG at different magnifications (right). GRFG was prepared by increasing the reactant concentrations in the water / ethanol mixture by 25-fold, in contrast to the preparation of GRF, while maintaining the resorcinol:formaldehyde:Fe(acac) 2 Even though the spherical morphology of carbon is lost, GRFG still has the high graphitization and mesoporous texture of GRF, which highlights the excellent scalability of this reaction.

[0055] As shown in Figure 12, a simplified reaction scheme for the polycondensation of resorcinol and formaldehyde is shown, along with an overview of different synthetic routes for RF spheres or RF gels.

[0056] Since RF polymerization is highly sensitive to pH, the latter was measured 15 min after complete dissolution of the reactants. Figure 2 In the present study, the texture of the polymers for different salts is compared with the reference salt and the pH of the respective synthesis mixtures. Due to the low solubility of ferric acetylacetonate in water, the mixtures are not completely clear and therefore the measured pH represents the value of a saturated solution of the salts. As expected, the effect of the acidic iron salts on the pH of the reaction mixture is significant. For FeCl 3 and Fe(NO 3 ) 3 For both, the pH moves from about 11 to 2 for the reference without iron salts, which completely changes the behavior of the reaction. Macroscopically, this manifests as a dense polymer that cannot be dispersed, so the successful formation of uniform spherical particles can be excluded. For all other salts, the pH remains in the alkaline region and an orange powder is obtained after filtration and drying. Since the color of the powder is significantly darker, it can be expected that the polymer contains iron. In particular, the reaction involving ferric acetylacetonate is promising because the salt hardly affects the pH of the mixture.

[0057] In addition Figure 3 In the figure, the original state is shown after carbonization and after leaching, with Fe(acac) 2 Preparation of RF polymers 2 Comparison of physical adsorption isotherms (left) and XRD patterns (right). For the "leached" and "carbonized" states, the intensity of the XRD patterns is normalized to the (002) reflection of graphite (~26°), while the patterns derived from polymer analysis are plotted as absolute intensity. After graphitization, a significant increase in porosity is observed. In addition, the (002) reflection (~26°) in the XRD pattern indicates the formation of graphitic carbon.

[0058] In the following section, CRF-S-Fe(acac) is investigated in more detail. x First, the inventors scaled up the synthesis 10-fold to a 1 L flask, which produced about 6 g of iron-containing polymer in one batch. In addition, the inventors replaced the hydrothermal treatment (24 hours at 100 ° C in a Teflon-lined autoclave) with stirring at 70 ° C for 24 hours, which significantly reduced the complexity, especially for larger quantities. Figure 4 As shown in the TEM micrographs, CRF-Fe(acac) 2 and CRF-Fe(acac) 3is mesoporous and highly graphitized. In fact, the synthesis at lower temperatures but under stirring enables the preparation of carbon spheres with narrower size distributions than those prepared using the solvothermal step, e.g. for CRF-Fe(acac) 3 For example, it is 367±32nm.

[0059] Figure 5 N 2 Characterization of physical adsorption, XRD and Raman spectroscopy.

[0060] In order to study the formation of the mesoporous system in the two samples prepared with iron acetylacetonate, Figure 6 Starting from the non-porous polymer shown, TG-MS measurements were performed in argon.

[0061] like Figure 7 Figure 2 shows the GRF prepared using Co and Ni acetylacetonate with N 2 Characterization of physical adsorption. The isotherms shown are similar to those of the material prepared using Fe(acetylacetonate), with the porosity of the carbon being primarily in the mesoporous range expected for ORR catalysts, but not when using Ni(acac) 2 As a salt, a material with an overall lower porosity is obtained.

[0062] CRF-Fe(acac) 2 and CRF-Fe(acac) 3 The optimized synthesis yielded highly graphitized mesoporous carbon spheres. The preparation sequence was a one-pot reaction followed by filtration, drying at 80 °C in air and carbonization under an inert atmosphere, followed by leaching with HCl. This procedure was very simple compared to the literature, which prompted a shift to the use of iron acetylacetonate as a combined porogen and graphitizing agent. To demonstrate that CRF-Fe(acac) 2 To investigate the suitability of GRF (from now on referred to as GRF) as a support for PEMFC catalysts, the present inventors loaded it with Pt NPs as follows: 2 PtCl 6 Incipient wetness impregnation (IWI) of aqueous solution followed by reduction and annealing. Variation of the annealing temperature was performed to determine the appropriate conditions to produce 3 nm diameter platinum particles. Figure 8 The XRD patterns and TEM micrographs of the final selected Pt / GRF annealed at 750°C are summarized. The samples annealed at different temperatures have the expected Pt reflections in the XRD patterns. As expected, there is a trend towards sharper reflections with increasing temperature, which is clearly visible in the (111) reflection. From the TEM micrographs, small particles of about 3 nm dispersed on the carbon are shown.

[0063] like Fig. 9As shown, Pt / GRF was evaluated as a catalyst for ORR in a rotating disk electrode setup. The reader is referred to the Experimental section for details on the electrochemical characterization. The specific activity (SA), mass activity (MA), and electrochemical surface area (ECSA) are summarized in Fig. 9 The activity and ECSA of Pt / GRF are in good agreement with the values ​​expected from the literature and are essentially determined by the size of the Pt NPs. However, NPs of around 3 nm present a good compromise between high mass activity and stability, as NPs below 2 nm are prone to enhanced dissolution. The stability of Pt / GRF was studied in an accelerated degradation protocol over the common voltage range of PEMFCs, 0.6-1.0 V (RHE). Compared to a catalyst consisting of platinum NPs (Pt / V) on Vulcan, Pt / GRF retains a significantly higher fraction of its ECSA after extended cycling ( Fig. 9 ). This indicates that the Pt NPs were successfully confined within the mesopores of GRF, which prevented the agglomeration and segregation of the active metals.

[0064] exist Fig.10 In the figure, the XRD patterns of GRF and GRFG (upper left) and N 2 Comparison of physical adsorption (lower left) data, and micrographs of GRFG at different magnifications (right). GRFG was prepared by increasing the reactant concentrations in the water / ethanol mixture by 25-fold, in contrast to the preparation of GRF, while maintaining the resorcinol:formaldehyde:Fe(acac) 2 ratio and ammonia concentration. Even though the spherical morphology of carbon is lost, GRFG still has the high graphitization and mesoporous texture of GRF, which highlights the excellent scalability of this reaction. Similar to GRF, GRFG is highly graphitized and has almost the same porosity.

[0065] Experimental Section

[0066] Description of the method

[0067] High-resolution transmission electron microscopy (HR-TEM) images were obtained on a HF-2000 microscope equipped with a cold field emitter (CFE) and operated at a maximum accelerating voltage of 200 kV. Typically, the samples were placed on Lacey carbon films supported on a copper grid. Solid samples were deposited on the Lacey carbon films without prior dissolution.

[0068] Room temperature XRD patterns were collected using a Bragg Brentano diffractometer (STOE THETA / THETA). The instrument was equipped with a secondary graphite monochromator (CuKα 1,2Radiation) and a proportional gas detector. The divergence slit was set to 0.8°, the receiving slit was set to 0.8 mm, and the width of the horizontal mask was 6 mm. The samples were prepared on a single crystal quartz sample holder without background.

[0069] Thermal analysis (thermogravimetric analysis, TG) coupled to mass spectrometry (MS) was performed on a Netzsch STA 449F3 Jupiter thermal analysis instrument connected to a Netzsch QMS 403D Aeolos mass spectrometer. The sample (about 10 mg) was heated in a continuous flow of argon (40 mL min -1 ) from 45°C to 1000°C (heating rate 10°C min -1 ).

[0070] Nitrogen adsorption isotherms were recorded using a Micromeritics 3Flex instrument. The apparent specific surface area was estimated by applying the Brunauer-Emmet-Taylor (BET) algorithm. The micropore volume and external surface area were determined using the t-plot method. Carbon black STSA was used as the thickness curve. The Gurvich rule was used at 0.95 p / p 0 The total pore volume was determined.

[0071] Inductively coupled plasma optical emission spectroscopy (ICP-OES) analysis was performed on a Spectrogreen FMX 46 using a UVPIus Optic ORCA (optimized Rowland circle alignment) optical system. To prepare the liquid sample for the measurement, about 10 mg of the catalyst was dissolved in 7.5 mL of HCl, 2.5 mL of HNO 3 and 0.8 mL of H 2 O 2 The suspension was heated in an AntonPaar Multiwave 5000 microwave oven at 180°C for 5 minutes and then allowed to cool naturally to ambient temperature. Then, after dilution to 50 mL with mQ water and stirring overnight, the analysis was performed and the metal concentration was evaluated. Throughout the procedure, the weight of the sample was measured using a Mettler Toledo XA205 dual range and a Sartorius Entris II.

[0072] Electrochemical measurements

[0073] The specific activity (SA) and mass activity (MA) for ORR, as well as the electrochemical surface area (ECSA) were evaluated by electrochemical half-cell measurements in a three-electrode compartment Teflon cell using a rotating disk electrode (RDE) setup. A graphite rod was used as the counter electrode, and a double junction Ag / AgCl (3M KCl, Metrohm) electrode was used as the reference electrode. The cell compartment of the reference electrode was separated by a Nafion membrane to avoid the leaching of chloride ions during the activity and stability measurements. All potentials are given relative to the reversible hydrogen electrode (RHE). To ensure accurate calibration of the Ag / AgCl electrode potential, the potential of the Ag / AgCl electrode was measured in advance with the addition of a Nafion membrane. 2 The potential was measured with the aid of a Pt electrode in a saturated electrolyte. This procedure was repeated for each activity and stability measurement with the tested Pt-based ORR catalyst as RHE.

[0074] The catalyst membrane was prepared by first dispersing the catalyst powder in ultrapure water (VWR) using an ultrasonic vial processor. Then, after an initial treatment of 30 min, a 20 μL droplet of ink was pipetted onto a 5 mm (0.196 cm) diameter Teflon shell embedded in a 2 The amount of catalyst on the electrode was 10 μg cm based on the Pt loading relative to the carbon support and dispersion. -2 For both activity and stability measurements, 0.1 M HClO 4 (By diluting 70% HClO with ultrapure water 4 Ultrapure (Carl Roth) was used as the electrolyte. The ohmic drop was corrected by positive feedback to keep the residual uncompensated resistance below 3Ω.

[0075] Before each activity and stability measurement, the catalyst was heated in N 2 The ORR activity was analyzed by Koutecky-Levich analysis at 0.9 V / RHE and a rotation frequency of 1600 rpm from O 2 The anodic scan of the CV recorded in saturated electrolyte was calculated with a scan rate of 50 mV s -1 The CVs were corrected for capacitive processes by subtracting the CVs recorded in nitrogen within the same potential window to isolate the current involved in oxygen reduction. The specific activity (SA) is given as the kinetic current density normalized to the real surface area, which is derived from the electrochemical CO oxidation charge. For this purpose, the CVs recorded in N were subtracted from the CVs recorded in N. 2 After recording the CV in saturated electrolyte, the peak of the CO stripping CV was integrated to correct for non-Faradaic contributions. A surface charge density of 380 μC cm was assumed.-2 Pt The electrochemical surface area (ECSA) was calculated. The mass activity (MA) was derived from the SA and ECSA. The stability was measured based on the 1 V s -1 The degradation test was performed on N 2 The experiments were performed in saturated electrolyte without rotation and the ECSA was determined by CO stripping.

[0076] Synthesis of RF carbon spheres

[0077] The synthesis of RF carbon spheres is based on the goal of obtaining uniform RF spheres. Type of method. Typically, 40ml water, 16ml ethanol and 0.20ml ammonia solution (25wt% aqueous solution) are mixed for 5 minutes. Subsequently, 0.40g resorcinol and a certain amount of iron salt (making the molar ratio of iron to resorcinol be 1:3) are dissolved in the mixture under stirring. The pH measurement of the reaction mixture is carried out at this stage. Then, 0.56mL formaldehyde (37wt% aqueous solution with 10-15% methanol) is added to the solution, which is further stirred at 30°C for 24 hours. After this step, for a sample called CRF-S-SALT, the reaction mixture is transferred to an autoclave with a teflon inlet and solvent-thermally treated at 100°C for 24 hours without stirring. For a sample called CRF-SALT, the solvent-thermally treated is replaced by stirring the reaction mixture at 70°C for 24 hours in a round-bottom flask equipped with a reflux condenser. After two procedures, the solid is filtered, washed with water and ethanol, and dried overnight in air at 80°C. If not otherwise stated, carbonization was carried out at 1000 °C in a tube furnace at 100 mL min -1 4 hours in an argon stream. After cooling naturally to room temperature, the iron residue in the black solid was leached in semi-concentrated HCl at 60 ° C overnight, twice. Finally, the powder was washed with a large amount of water and ethanol and dried in air at 80 ° C. Using the above reactant amounts, a yield of about 600 mg of polymer and a final yield of about 200 mg of carbon was obtained. In order to prepare the CRF-SALT sample, the reaction was scaled up 10 times.

[0078] Exemplary synthesis of RF carbon gel

[0079] To prepare the RF gel, 13.75 mL of water, 5.52 mL of ethanol, and 0.063 mL of ammonia solution (25 wt% aqueous solution) were mixed in a 50 mL PE bottle for 5 minutes. Subsequently, 3.00 g of resorcinol and 2.29 g of Fe(acac) were dissolved under stirring. 2, which gives a molar ratio of iron to resorcinol of 1:3. After complete dissolution, 4.06 mL of formaldehyde solution (37 wt % aqueous solution containing 10-15% methanol) is added. The sealed bottle is then stirred at 50°C for 2 hours and then at 70°C for 24 hours. The mixture solidifies after about 6 hours and stirring is stopped. The bottle is then opened and the orange gel is dried at 80°C in air overnight. After drying, the polymer monolith is crushed and ground to produce an orange powder, which is carbonized and leached according to the procedure described for RF carbon spheres.

[0080] Preparation of Pt / GRF

[0081] According to our recent literature on the synthesis of Pt / HGS, GRF was loaded with Pt NPs. Briefly, 100 mg of GRF was dried overnight under vacuum. 2 PtCl 6 The powder was impregnated with a solution in which the amount of water was equal to 90% of the total pore volume of the carbon. The impregnation was performed in three steps of equal volume under strong stirring and shaking. To ensure that the pores were completely filled, the powder was sonicated for 30 minutes. The powder was dried, reduced and annealed in a tube furnace. The sample was heated at 120 °C (3K min -1 ) in an argon flow (200 mL min -1 ) for 60 minutes and then dried at H 2 and Ar mixture (40 / 160mL min -1 )Heat to 220℃(3K min -1 ) for 90 min. Finally, the powder was stirred in an Ar atmosphere (100 mL min -1 ) annealed at different temperatures for 2.5 hours (5Kmin -1 ).

[0082] Summarize

[0083] As described above, the carbon materials prepared by the method of the present invention include CRF-Fe(acac) x , presenting spherical, mesoporous and highly graphitized carbon, and therefore is a candidate for further study and ultimately for use as a catalyst support for electrochemical devices. The inventors believe that due to the high affinity of the acetylacetonate anion for metal cations, metal salts such as Fe(acac) x Incorporated into the carbon structure, this behaves as a ligand that does not dissociate in solution. This behavior is evident from the pH effect described earlier and the low water solubility of the salt. The latter would make incorporation into the polymer easier, as both the ferric acetylacetonate and the polymer are expected to have similar hydrophilicity.

[0084] CRF - transition metal salt such as Fe(acac)2 The optimized synthesis produces highly graphitized mesoporous carbon spheres. The preparation sequence is a one-pot reaction followed by filtration, drying at 80 °C in air and carbonization under inert atmosphere, followed by leaching with HCl. This procedure is very simple compared to the literature, which has led to a shift to the use of iron acetylacetonate as a combined porogen and graphitizing agent. To demonstrate that CRF-Fe(acac) 2 To investigate the suitability of GRF (from now on referred to as GRF) as a support for PEMFC catalysts, the present inventors loaded it with Pt NPs as follows: 2 PtCl 6 Incipient wetness impregnation (IWI) of aqueous solution followed by reduction and annealing. Variation of annealing temperature was performed to determine suitable conditions to produce 3 nm diameter platinum particles. The formed catalyst Pt / GRF was evaluated as a catalyst for ORR and exhibited high activity and stability, which was directly formed by the beneficial structure of the carbon support.

[0085] Although the synthesis of GRF is simplified compared to the general literature, the high degree of control of the morphology, i.e. the preparation of uniform carbon spheres, is accompanied by the disadvantage of a relatively high dilution of the synthesis mixture. Using the current protocol, about 2 g of carbon per liter can be prepared. For industrial purposes, it is desirable to increase the volumetric yield of the preparation. Therefore, the present inventors increased the concentration of resorcinol and formaldehyde by 25 times compared to the synthesis of GRF, while maintaining the NH 3 concentrations and ethanol / water and Fe / resorcinol ratios. The polycondensation was carried out at 70°C for 24 hours under stirring, but stirring was stopped after 6-8 hours by solidification of the gel, which produced a polymer gel that was subsequently dried in air at 80°C. After carbonization and leaching, the inventors obtained a highly graphitized carbon gel (GRFG) whose physical properties were very similar to those of spherical GRF. Similar to GRF, GRFG is highly graphitized and has almost the same porosity. However, iron particles confined in graphite shells are present throughout the structure. According to the results of the carbonization reaction in aqua regia and H at elevated pressure, the GRFG was characterized by a high degree of graphitization and a high porosity. 2 O 2 ICP-OES measurements performed after heating the mixture of GRF and GRFG to decompose the carbon (see the Experimental section for details) determined that the iron content of both GRF and GRFG was less than 1 wt%.

[0086] Considering the similar performance in terms of graphitization and porosity, GRFG presents an even more promising catalyst support than GRF. The increase in volumetric productivity to about 70 g carbon per liter removes the last obstacle that prevents GRFG from being successfully used as a PEMFC support with industrial application potential.

[0087] As shown above, the inventors have developed a synthetic route to graphitic mesoporous carbon starting from the established resorcinol formaldehyde chemistry. Using iron salts, in particular acetylacetonate, as graphitization catalyst and porogen, the inventors prepared uniform carbon spheres that exceed most carbon blacks in their share of graphitic carbon. In addition, the carbon has intraparticle mesoporosity, a property rarely found in RF materials. Taking advantage of this useful pore structure, the inventors loaded the carbon with Pt NPs, thus preparing a highly active electrocatalyst for oxygen reduction reactions, which, most importantly, has enhanced stability compared to industrial catalysts. A clear advantage of the procedure is its simplicity. In addition, since no complex drying, templating or activation is required, it seems promising to scale up the procedure to even higher product quantities. In fact, the inventors demonstrated that the procedure is open to significant optimization when the inventors increased the reaction concentration by 25 times and still obtained graphitic mesoporous carbon with an industrially relevant volumetric yield of 70 g carbon / liter of synthesis mixture.

Claims

1. A method for preparing graphitized nanoporous carbon, comprising the steps of: a) Prepare the following mixture in a solvent: i) a nucleophilic compound selected from the group consisting of melamine, melam, melem, ammeline, 4,6-amino-dihydroxy-1,3,5-triazine, aminophenol, diaminobenzene, dihydroxybenzene, trihydroxybenzene and any combination thereof, ii) formaldehyde or an oligomer thereof in a stoichiometric excess relative to compound i) for complete polymerization, iii) a metal graphitization catalyst, wherein the molar ratio of the metal graphitization catalyst to compound i) is from 1:30 to 1:3, optionally from 1:10 to 1:3, wherein the metal graphitization catalyst is selected from Fe salts, Co salts or Ni salts of organic acids or acidic organic compounds, in particular Fe formate, Fe oxalate, Ni oxalate, Ni formate, Co oxalate, Co formate, Fe(II)(acac)2, Fe(III)(acac)3, Ni(II)(acac)2, Co(II)(acac)2, Co(III)(acac)3 or any combination thereof, and optionally iv) a catalytic amount of a promoter compound, preferably ammonia, The solvent comprises water and a C1-C3 aliphatic alcohol, wherein the volume ratio of water is 0 volume %-100 volume % relative to the total volume of the solvent, and the balance is the C1-C3 aliphatic alcohol; the solvent is preferably an aqueous solution having a content of 10-40 volume % of the C1-C3 aliphatic alcohol; b) heating the mixture obtained in step a) to a temperature of 30° C. to 100° C. and maintaining the mixture in this temperature range for at least 6 hours, preferably 6 to 60 hours, more preferably 6 to 50 hours, c) separating the reaction product obtained in step b) from the aqueous solvent, optionally grinding the separated reaction product and optionally washing the separated reaction product with fresh aqueous solvent; d) subjecting the separated reaction product obtained in step c) to a high temperature graphitization process at a temperature ranging from 600° C. to 1000° C., thereby providing a graphite skeleton; e) subjecting the graphitized product obtained in step d) to a process for leaching out the metal of the metallic graphitization catalyst, preferably by treatment with a mineral acid; and f) washing the reaction product obtained in step e) with water and a C1-C3 aliphatic alcohol and finally drying the washed product, followed by an optional grinding step.

2. A method for preparing graphitized nanoporous carbon according to claim 1, comprising the further steps of: g) impregnating the graphitized nanoporous product obtained in step f) with a catalytically active metal selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Mo, Se, Sn, Pt, Ru, Pd, W, Ir, Os, Rh, Nb, Ta, Pb, Bi, Au, Ag, Sc or Y, preferably Pt, Ru, Pd, Au, Ag, Ni, Co or Ir, including their salts and mixtures thereof, in the form of a solution of the metal salt or mixtures thereof, preferably by incipient wetness, h) subjecting the graphitized nanoporous product obtained in step g) to a hydrogenation process, thereby forming catalytically active metal sites; i) subjecting the graphitized nanoporous product obtained in step h) to a further temperature treatment in an atmosphere inert to the metal particles and the graphitized nanoporous product at a high temperature range of 600°C to 1400°C, preferably 600°C to 1000°C, thereby changing the microstructure and confining the catalytically active metal sites in the mesopores, thereby improving the chemical and electrochemical properties.

3. A method for preparing graphitized nanoporous carbon according to any one of claims 1 or 2, wherein the compound i) is selected from resorcinol, melamine and its derivatives, in particular resorcinol.

4. A method for preparing graphitized nanoporous carbon according to any one of claims 1 to 3, wherein the metal graphitization catalyst is selected from Fe(II)(acac)2, Fe(III)(acac)3, Ni(II)(acac)2, Co(II)(acac)2, Co(III)(acac)3 or any combination thereof.

5. The method for preparing graphitized nanoporous carbon according to any one of the preceding claims, wherein the concentration of compound i) in the solvent is 0.01 mol / L to 0.5 mol / L, and the mixture is stirred in step b).

6. A method for preparing a graphitized nanoporous carbon according to any one of the preceding claims, wherein the concentration of compound i) in the aqueous solvent is 0.5 mol / L to 2.0 mol / L, and the mixture is not stirred in step b).

7. Graphitized nanoporous carbon particles obtainable by the method according to any one of claims 1 to 6.

8. Use of the graphitized nanoporous polymer particles according to claim 7 as a catalyst, in particular for the cathode-side oxygen reduction reaction (ORR) in a PEM fuel cell.

Citation Information

Patent Citations

  • Highly sinter-stable metal nanoparticles supported on mesoporous graphitic particles and their use

    WO2013117725A1